Vulnerability assessment of android instant messaging application and network intrusion detection prevention systems. Issue 2 (17th February 2020) - Gaharwar, Ratan Singh; Gupta, Roopam
Abstract: The amount of data, due to the quantum leap of technology, generated, processed, transmitted and stored is huge, heterogeneous, unconditional and unpredictable. The data exchanging using smart devices communication is rapidly enhancing so for effective and efficient data transmissions are very essential. The instant massage applications are very highly used applications for exchanging the information hence it is very essential for instant messaging application to be vulnerability free applications. In this paper a detailed study is discussed on vulnerability assessment in instant Messaging applications as well as also discusses intrusion detection prevention methodologies. In the view of data leakage detection, instant massage exchanging and contact details storage can be examined for each application. In this work a comprehensive reverse engineering is discussed with different smart phones and mobile OS. Smart phones are the most popular and useable communication device in which different types of data are processed by which it can be classified as public and private. It is a very essential concept to evaluate the applications that are used to infiltrate very sensitive data from smart phones such as contact details, location details, communication massage data, pictures and other confidential information. It is necessary to deploy a vulnerability protected system in smart phones which prevent the data leakage from malicious applications. The major challenge in to save the data and protect the access control system when the system transfers the data through data exchanging applications. Malicious applications can access the control and causes data leakage. In this paper the smart phone based instant messaging applications evaluated and examines the data leakage. For this Android based smart phones chosen with a dedicated vulnerability assessment tool kit. In this paper vulnerability assessment and simulation are discussed in detail so that instant messaging applications become more secured and free from vulnerability.